Preparation and near-infrared photothermal conversion property of cesium tungsten oxide nanoparticles - Chen, Cheng-Jia (Springer, 2013)
Cs(0.33)WO(3) nanoparticles have been prepared successfully by a stirred bead milling process. By grinding micro-sized coarse powder with grinding beads of 50 μm in diameter, the mean hydrodynamic diameter of Cs(0.33)WO(3) powder could be reduced to about 50 nm in 3 h, and a stable aqueous dispersion could be obtained at pH 8 via electrostatic repulsion mechanism. After grinding, the resulting Cs(0.33)WO(3) nanoparticles retained the hexagonal structure and had no significant contaminants from grinding beads. Furthermore, they exhibited a strong characteristic absorption and an excellent photothermal conversion property in the near-infrared (NIR) region, owing to the free electrons or polarons. Also, the NIR absorption and photothermal conversion property became more significant with decreasing particle size or increasing particle concentration. When the concentration of Cs(0.33)WO(3) nanoparticles was 0.08 wt.%, the solution temperature had a significant increase of above 30°C in 10 min under NIR irradiation (808 nm, 2.47 W/cm(2)). In addition, they had a photothermal conversion efficiency of about 73% and possessed excellent photothermal stability. Such an effective NIR absorption and photothermal conversion nanomaterial not only was useful in the NIR shielding, but also might find great potential in biomedical application.